2013
DOI: 10.7241/ourd.20133.65
|View full text |Cite
|
Sign up to set email alerts
|

A survey of nail infection and awareness among non-diabetic patients in Mauritius

Abstract: Introduction: Nail infection like onychomycosis is mainly caused by dermatophytes and account for almost half of all nail disorders. Prevalence of nail infection has been attributed to several factors such as age, gender, socioeconomic status and predisposition to diabetes amongst others. This study aims at determining the prevalence and level of awareness of non-diabetics towards nail infections in Mauritius. Material and Methods: A survey was carried out among 471 participants of the non-diabetic population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a study carried out on nondiabetic patients, it was found that there is no significant relationship between fungal infection in nails and level of education. It depended upon manual handwork practice, occupation and quality of life, socioeconomic status, gender, and age [ 27 ]. However, our study shows that there are no fungal isolates from participants with a master level of education in both study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out on nondiabetic patients, it was found that there is no significant relationship between fungal infection in nails and level of education. It depended upon manual handwork practice, occupation and quality of life, socioeconomic status, gender, and age [ 27 ]. However, our study shows that there are no fungal isolates from participants with a master level of education in both study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of fungal infection is higher in sultry humid climates and in crowded living conditions 22 . The differences in the incidence of superficial infections between the age groups and genders may be reflected the differing rates of sebum production and fluctuations of immunity with aging 21 .…”
Section: Figure (1) Distribution Of Patients With Dermatophytes According To Their Educationmentioning
confidence: 99%